Early Vocabulary Development of Australian Indigenous Children: Identifying Strengths. (1st April 2014) - Farrant, Brad M.; Shepherd, Carrington C. J.; Walker, Roz D.; Pearson, Glenn C.
Abstract : The current study sought to increase our understanding of the factors involved in the early vocabulary development of Australian Indigenous children. Data from the Longitudinal Study of Indigenous Children were available for 573 Indigenous children (291 boys) who spoke English (M = 37.0 months, S D = 5.4 months, at wave 3). Data were also available for 86 children (51 boys) who spoke an Indigenous language (M = 37.1 months, S D = 6.0 months, at wave 3). As hypothesised, higher levels of parent-child book reading and having more children's books in the home were associated with better English vocabulary development. Oral storytelling in Indigenous language was a significant predictor of the size of children's Indigenous vocabulary.